Resilience and the Cultural Landscape : Understanding and Managing Change in Human-Shaped Environments - Plieninger, Tobias, editor; Bieling, Claudia, editor (Cambridge, UK ; New York : Cambridge University Press, 2012)
"All over the world, efforts are being made to preserve landscapes facing fundamental change as a consequence of widespread agricultural intensification, land abandonment and urbanisation. The 'cultural' and 'resilience' approaches have, until now, largely been viewed as distinct methods for understanding the effects of these dynamics, and the ways in which they might be adapted or managed. "